The Influence of Influencer Marketing on Tiktok on the Purchase Intention of PT. Cosmax Indonesia Skincare Products - Putik Mutia Amani; Anna Amalyah Agus (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to analyze the impact of influencer marketing on TikTok on consumers' purchase intention towards skincare products from PT Cosmax Indonesia. Using the Stimulus-Organism-Response (SOR) model approach, this research examines influencer characteristics such as attractiveness, expertise, originality, homophily, and interaction as stimuli affecting consumer attitudes, including image satisfaction and advertising trust, as well as self-brand connection towards purchase intention. Additionally, product attributes such as product quality, ingredients, awareness, and safety are also analyzed for their impact on purchase intention. Data were collected from 388 respondents who are active TikTok users aged 18–34 years and regularly use skincare products. A quantitative method through questionnaires was employed, and the data were analyzed using SEM-PLS (SmartPLS 4). The results of the study show that all influencer characteristics significantly influence advertising trust and image satisfaction. Advertising trust was found to have a direct impact on purchase intention, whereas image satisfaction and self-brand connection did not directly influence purchase intention. On the other hand, product attributes, especially product safety, were the most dominant factor in driving purchase intention. The results of the Multigroup Analysis also revealed that there were no significant differences between the preferences for educational and entertainment content in influencing the relationships among the variables. This study emphasizes the importance of influencer credibility and product quality as the primary strategies for influencing purchase decisions on TikTok.